Resistance training prevents damage to the mitochondrial function of the skeletal muscle of rats exposed to secondary cigarette smoke - Moreno, Ana Caroline Rippi [UNESP] (2022)
Aim: To analyze the consumption of oxygen and to quantify the mitochondrial respiratory chain proteins (OXPHOS) in the gastrocnemius muscle of rats exposed to cigarette smoke and/or RT practitioners. Main methods: Wistar rats were divided into groups: Control (C), Smoker (S), Exercise (E) and Exercise Smoker (ES). Groups F and ES were exposed to the smoke of 4 cigarettes for 30 min, 2× a day, 5× a week, for 16 weeks. Groups E and ES performed four climbs with progressive load, 1× per day, 5× per week, for 16 weeks. The gastrocnemius muscle was collected for analysis of OXPHOS content and oxygen consumption. Groups S (vs. C) and ES (vs. C and E) showed lower body weight gain when observing the evolution curve. Key findings: The S rats showed a reduction in the NDUFB8 proteins of complex 1, SDHB of complex 2, MTC01 of complex 4 and ATP5A of complex 5 (ATP Synthase) compared to Group C. Additionally, S rats also showed increased consumption of O2 in Basal, Leak, Complex I and I/II combined measures compared to the other groups, suggesting that the activity of the mitochondria of these animals increased in terms of coupling and uncoupling parameters. Significance: Our data suggest that exposure to cigarette smoke for 16 weeks is capable of causing impairment of mitochondrial function with reduced expression of respiratory chain proteins in skeletal muscle. However, the RT was effective in preventing impairment of mitochondrial function in the skeletal muscle of rats exposed to secondary cigarette smoke.